An axiomatization of the proportional rule in financial networks - Péter Csóka; P. Jean-Jacques Herings (Hungarian Academy of Sciences, Institute of Economics, 2016)
The most important rule to determine payments in real-life bankruptcy problems is the proportional rule. Many bankruptcy problems are characterized by network aspects and default may occur as a result of contagion. Indeed, in financial networks with defaulting agents, the values of the agents' assets are endogenous as they depend on the extent to which claims on other agents can be collected. These network aspects make an axiomatic analysis challenging. This paper is the first to provide an axiomatization of the proportional rule in financial networks. Our two central axioms are impartiality and non-manipulability by identical agents. The other axioms are claims boundedness, limited liability, priority of creditors, and continuity.
Keywords: C71; G10; 330; financial networks; systemic risk; bankruptcy rules; proportional rule